Optimalisasi Manajemen Masjid pada Masjid Aisyah Islamic Center Al-Hunafa Lawata sebagai Lembaga Dakwah dan Pendidikan Islam - M. Tahir (LP2M STIT Palapa Nusantara, 2022)
The mosque of Aisyah Islamic Center Al-Hunafa Lawata has a multifunctional role , such as a center of workship, da’wah and education. As a worship center, it is open to local residents and the public for both obligatory and recommended prayers and I’tikaf. Also, it is a da’wah center where it is used for routine studies carried out after dawn and dusk prayers. Additionally, its role as a center for formal and non-formal education was accomplished through the establishment of the Religious High School (MAK) and the Qur’an Education Park (TPA). In additionally, this place is a center of social activities like the distribution of nine main food and qurban meat as well as providing free iftar in Ramadhan. Ths study is qualitative where the mosque administrators are the main data sources gathered using observation, interviews, and documentation. Data mining is closely related to the formulation of research problemswhich is how the role and management of the mosque as a center of da’wah and education. The study found that the mosque remains a multifunctional place as a center of worship da’wah, and formal and non-formal education and has developed as social service activities. The overall optimization of the mosque’s role is carried out by optimizing all management function including planning, actuating or implementing, organizing, and evaluating as well.